ANX7 as a Bio-Marker in Prostate and Breast Cancer Progression. Issue 2 (13th June 2013) - Srivastava, Meera; Bubendorf, Lukas; Nolan, Lisa; Glasman, Mirta; Leighton, Ximena; Miller, Georgina; Fehrle, Wilfred; Raffeld, Mark; Eidelman, Ofer; Kallioniemi, Olli P.; Srivastava, Shiv; Pollard, Harvey B.
Abstract : The ANX7 gene codes for a Ca 2+ -activated GTPase, which has been implicated in both exocytotic secretion in cells and control of growth. In this review, we summarize information regarding increased tumor frequency in the Anx7 knockout mice, ANX7 growth suppression of human cancer cell lines, and ANX7 expression in human tumor tissue micro-arrays. The loss of ANX7 is significant in metastatic and hormone refractory prostate cancer compared to benign prostatic hyperplasia. In addition, ANX7 expression has prognostic value for predicting survival of breast cancer patients.